Nitrogenous disinfection byproducts in English drinking water supply systems: occurrence, bromine substitution and correlation analysis - Bond,T; Templeton,MR; Mokhtar,Kamal NH; Graham,NJD; Kanda,R (Water Research, 2015)
Despite the recent focus on nitrogenous disinfection byproducts in drinking water, there is limited occurrence data available for many species. This paper analyses the occurrence of seven haloacetonitriles, three haloacetamides, eight halonitromethanes and cyanogen chloride in 20 English drinking water supply systems. It is the first survey of its type to compare bromine substitution factors (BSFs) between the haloacetamides and haloacetonitriles. Concentrations of the dihalogenated haloacetonitriles and haloacetamides were well correlated. Although median concentrations of these two groups were lower in chloraminated than chlorinated surface waters, median BSFs for both in chloraminated samples were approximately double those in chlorinated samples, which is significant because of the higher reported toxicity of the brominated species. Furthermore, median BSFs were moderately higher for the dihalogenated haloacetamides than for the haloacetonitriles. This indicates that, while the dihalogenated haloacetamides were primarily generated from hydrolysis of the corresponding haloacetonitriles, secondary formation pathways also contributed. Median halonitromethane concentrations were remarkably unchanging for the different types of disinfectants and source waters: 0.1 μg·mgTOC−1 in all cases. Cyanogen chloride only occurred in a limited number of samples, yet when present its concentrations were higher than the other N-DBPs. Concentrations of cyanogen chloride and the sum of the halonitromethanes were not correlated with any other DBPs.